2006
DOI: 10.1016/j.molcel.2006.09.019
|View full text |Cite|
|
Sign up to set email alerts
|

S6K1 Regulates GSK3 under Conditions of mTOR-Dependent Feedback Inhibition of Akt

Abstract: Feedback inhibition of the PI3K-Akt pathway by the mammalian target of rapamycin complex 1 (mTORC1) has emerged as an important signaling event in tumor syndromes, cancer, and insulin resistance. Cells lacking the tuberous sclerosis complex (TSC) gene products are a model for this feedback regulation. We find that, despite Akt attenuation, the Akt substrate GSK3 is constitutively phosphorylated in cells and tumors lacking TSC1 or TSC2. In these settings, GSK3 phosphorylation is sensitive to mTORC1 inhibition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
245
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(266 citation statements)
references
References 55 publications
21
245
0
Order By: Relevance
“…N, nucleus; C, cytoplasm; aNu, active nucleolus; cNu, cytoplasmic nucleolus; NM, nuclear membrane (also see Supplementary Figure S1) (e) Requirement of cisplatin, lithium chloride, and NEAA þ Vitamin deprivation to increase the number of blebbishields but to reduce necrosis Ser-9 in TSC-2 null cells without Akt activation. 15 Interestingly, p70S6K activation correlated with increased GSK-3b Ser-9 phosphorylation (Figure 1b).…”
Section: Resultsmentioning
confidence: 86%
“…N, nucleus; C, cytoplasm; aNu, active nucleolus; cNu, cytoplasmic nucleolus; NM, nuclear membrane (also see Supplementary Figure S1) (e) Requirement of cisplatin, lithium chloride, and NEAA þ Vitamin deprivation to increase the number of blebbishields but to reduce necrosis Ser-9 in TSC-2 null cells without Akt activation. 15 Interestingly, p70S6K activation correlated with increased GSK-3b Ser-9 phosphorylation (Figure 1b).…”
Section: Resultsmentioning
confidence: 86%
“…Finally, as a fourth possibility, we hypothesized that rapamycin resistance in Th2.R cells might be associated with inhibition of GSK3␤), which induces T cell apoptosis or cell cycle arrest (46). Of note, it has recently been shown that the mTOR and GSK3␤ pathways are interrelated (47). We found that the inactive, phosphorylated form of GSK3␤ was overexpressed in Th2.R cells relative to control Th2 cells (six of six cases).…”
Section: Th2 Cell Rapamycin Resistance: Evaluation Of Potential Mechamentioning
confidence: 78%
“…This was accompanied by transient activation of GSK-3b through dephosphorylation of Serine-9. Although, GSK-3b activity returned to normal in the presence of continued Akt inactivation involving other kinases such as S6K1 [29]. Thus, GSK-3b appears to be an arbiter of cell fate towards proliferation, arrest or apoptosis.…”
Section: Discussionmentioning
confidence: 94%